Cultural Adaptation, Translation and Psychometric Validation of a Technology and eHealth Literacy Questionnaire Among Albanian Undergraduate Nursing Students. - Fragkioudaki, Chrysi A.; Mechili, Enkeleint A.; Galanis, Petros; Patelarou, Evridiki; Giakoumidakis, Konstantinos; Patelarou, Athina E. (Nursing Reports, 2026)
Background: Rapid technological progress has transformed healthcare systems through integrating electronic health (eHealth) into clinical practice. Consequently, nursing students, upcoming healthcare professionals, face new challenges arising from this digital transition. Adequate technological skills and eHealth literacy are essential to meet the requirements of contemporary healthcare environments. The aim of this study was to translate, culturally adapt, and validate a questionnaire measuring technophilia, Internet use, eHealth literacy, and nursing students' attitudes toward technology and eHealth. Methods: A cross-sectional validation study was conducted using a convenience sample of Albanian undergraduate nursing students. After forward and backward translation, the instrument's construct validity was examined using exploratory factor analysis (EFA). Cronbach's alpha assessed internal consistency, and the relationships among the four constructs were explored using structural equation modeling (SEM). Results: A total of 357 undergraduate nursing students participated in the survey. EFA identified a clear four-factor structure corresponding to Technophilia, Internet Use, eHealth Literacy, and Technology and Electronic Health in Nursing Education, with all items demonstrating satisfactory factor loadings. Internal consistency of the four scales ranged from 0.692 to 0.852, indicating generally satisfactory reliability. Although the SEM model fit was below the recommended thresholds, the results provide some evidence for relationships among the constructs. Conclusions: The findings provide preliminary evidence for the reliability and validity of the adapted instrument and set a baseline for assessing Albanian nursing students' knowledge, skills, and attitudes regarding technology and eHealth literacy. Several strategies can be developed based on this evidence to prepare nursing students for technologically advanced healthcare systems.